Isolasi Bakteri Endofit Asal Padi Gogo dan Potensinya sebagai Agens Biokontrol dan Pemacu Pertumbuhan - Abdul Munif; Suryo Wiyono; Suwarno . (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Studies on endophytic bacteria has been increasing recently due to its potency to promote plant growth and induce plant tolerance to pests and diseases. The research was undergone to isolate endophytic bacteria from different varieties of upland rice from various growing regions in Indonesia, followed by evaluation of their biocontrol and plant growth activities. Isolation of endophytic bacteria was based-on surface-sterilized method using alcohol and NaOCl on trypsic soy agar (TSA) media. More than 200 isolates was successfully isolated and the selected isolates were subjected to in vitro assay for their ability to produce antibiotic and promote plant growth. The result showed 41 isolates of endophytic bacteria had antibiosis activity to Rhizoctonia solani, 25 isolates to Pyricularia grisea on potato dextrose agar (PDA) medium and 8 isolates showed antibiosis activity to both R. solani and P. grisea on both PDA and TSA. The result of plant growth test, showed 12 isolates of endophytic bacteria induced the growth of root and shoot of rice plant.This indicated that some of the endophytic bacteria have the potency as biocontrol agents and inducer of plant growth.Key words: endophytic bacteria, Pyricularia grisea, Rhizoctonia solani, upland rice